Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Pegawai Satuan Polisi Pamong Praja Kabupaten Karawang - Yuni Yuliantika; Aji Tuhagana; Zenita Apriani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to examine the effect of leadership and organizational culture on employee performance at the Karawang Regency Pamong Praja Police Unit. This analysis uses the independent variables of Leadership and Organizational Culture and the dependent variable is employee performance. The sample of this study were employees of the Karawang Regency Pamong Praja Police Unit. data collection was carried out by distributing questionnaires to employees whose respondents were 52 people. The analysis technique in this study used multiple linear regression methods. The results of this study indicate that there is no partial influence of leadership variables on employee performance, there is a positive and significant partial influence of organizational culture variables on performance, leadership and organizational culture together have a positive and significant effect on performance.